Grand sonata for the piano forte composed & dedicated to Prince Lichnowski by Louis van Beethoven ... op. 26 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (London; United Kingdom; Cramer, Beale & Co., 2022)
Edition of the Piano Sonata no. 12 in A-flat major, op. 26, published as "No. 2" in the series "Beethoven's Works edited by J. Moscheles, complete edition" by Cramer & Co. (201 Regent Street and 67 Conduit Street) in London between 1844-1861, in a revised reprint of the earlier edition published 1834 or 1835. Lithographed, with new plates for the third and fourth movements. At foot of title page: "NB In this edition, the utmost care has been taken to mark by Maelzel's metronome the author's time of each movement.